2023
DOI: 10.3389/fsurg.2022.1014781
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models for the risk and prognosis of bone metastasis in patients with newly-diagnosed esophageal cancer: A retrospective cohort study

Abstract: BackgroundEsophageal cancer (EC) is a common malignant tumor worldwide, and patients with both EC and bone metastasis (BM) have a poor prognosis. We aimed to determine the risk and prognostic factors for BM in patients with newly diagnosed EC and to conduct two nomograms to predict the probability of BM and overall survival after BM.MethodsData from patients with EC from 2010 to 2015 were reviewed in the Surveillance, Epidemiology, and End Results (SEER) database. We divided participants into training and vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(59 reference statements)
0
0
1
Order By: Relevance
“…Radiotherapy is considered effective in relieving pain caused by BM in cancer patients. Previous analyses focusing on the overall population of EC patients with bone metastasis indicated that radiotherapy was not an independent prognostic risk factor [9,25]. However, our study focusing on the ESCC patients with bone metastasis revealed a signi cant and protective association between radiotherapy and prognosis.…”
Section: Discussioncontrasting
confidence: 74%
“…Radiotherapy is considered effective in relieving pain caused by BM in cancer patients. Previous analyses focusing on the overall population of EC patients with bone metastasis indicated that radiotherapy was not an independent prognostic risk factor [9,25]. However, our study focusing on the ESCC patients with bone metastasis revealed a signi cant and protective association between radiotherapy and prognosis.…”
Section: Discussioncontrasting
confidence: 74%